Clinical characteristics, management and outcomes in patients with new onset or worsening acute heart failure enrolled in the nationwide BLITZ-HF study. (14th October 2021) - Orso, F; Di Lenarda, A; Oliva, F; Anselmi, M; Aspromonte, N; Di Tano, G; Leonardi, G; Lucci, D; Maggioni, A P; Mortara, A; Navazio, A; Pulignano, G; et al.
Abstract: Background: Real world observational clinical data is important to better characterize heterogeneous groups of patients, such those with acute heart failure (AHF), in order to phenotype patients with different prognosis and to generate hypotheses regarding management in clinical practice or patient selection for planning randomised clinical trials. Aims: To describe clinical characteristics, management and outcomes of acute heart failure (AHF) patients admitted for a first HF episode (de novo) or for worsening chronic HF (WHF) and enrolled by Italian cardiology sites participating to the nationwide BLITZ-HF study. Methods: BLITZ-HF was a prospective nationwide study based on a web-based recording system used during two enrollment periods (08/03/2017 – 04/09/2017 and 24/12/2017 – 09/04/2018). Overall, 7218 patients with acute and chronic HF were enrolled by 106 sites. Results: The present analysis refers to the 1470 out of 1494 patients admitted for AHF not lost to follow-up, of which 822 (56%) presented with de novo and 648 (44%) with WHF. Patients were followed for a median of 370 days [IQR 339–395]. Mean age was significantly higher in patients with WHF 74±12 (vs 72±12 in de novo, p<0.001), while no gender differences were observed (WHF 35% vs de novo 36%). Compared to de novo, patients with WHF had more frequently a history of treated hypertension (66% vs 61%, p=0.028), atrial fibrillation (52% vs 29%, p<0.0001), previous myocardial infarction and coronary revascularization (41% vs 19% and 38% vs 18% respectively, both p<0.0001), a previous device implantation (34% vs 6%, p<0.0001). Non cardiac comorbidities such as CKD and COPD resulted in a higher rate among patients with WHF (51% vs 28% and 26% vs 17%, both p<0.0001). We also found significant differences between the two groups in terms HF ejection fraction categories (HFrEF 64.5% vs 52.3%, HFmrEF 13.9% vs 21.4%, HFpEF 21.6% vs 26.3%, for WHF vs de novo, p<0.0001). On admission, patients with WHF presented with lower systolic blood pressure (124±27 vs 135±28, p<0.0001), lower hart rate (87±23 vs 95±26, p<0.0001), higher creatinine levels (1.5±0.7 vs 1.3±0.8, p<0.0001). Both inotropes and high dose of IV furosemide (>150 mg) were more frequently used among WHF patients (22.8% vs 9.7% and 35.7% vs 19.7%, p<0.0001). Figure and table show Kaplan-Meyer curves for one year all-cause mortality and detailed in-hospital and one-year outcomes regarding mortality (total and CV) and hospitalizations (all, CV and HF) as well as the combined outcome of HF hospitalization and all-cause mortality. Patients with WHF had significantly worse outcomes compared to those with de novo HF. Conclusions: In our study we confirm the heterogeneity of AHF patients and the importance of identify and characterize different subgroups. Patients with WHF have a more severe clinical profile and worse in-hospital and one-year clinical outcomes. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The study was funded by Heart Care Foundation with a partial unrestricted support from Abbott, Daiichi Sankyo, Medtronic, Servier, Vifor.